Quality Assessment of Online Patient Information for Cosmetic Botulinum Toxin. (18th June 2020) - Barbarite, Eric; Shaye, David; Oyer, Samuel; Lee, Linda N
Abstract: Background: In an era of widespread Internet access, patients increasingly look online for health information. Given the frequency with which cosmetic botulinum toxin injection is performed, there is a need to provide patients with high-quality information about this procedure. Objectives: The aim of this study was to examine the quality of printed online education materials (POEMs) about cosmetic botulinum toxin. Methods: An Internet search was performed to identify 32 websites of various authorship types. Materials were evaluated for accuracy and inclusion of key content points. Readability was measured by Flesch Reading Ease and Flesch-Kincaid Grade Level. Understandability and actionability were assessed with the Patient Education Materials Assessment Tool for Printed Materials. The effect of authorship was measured by undertaking analysis of variance between groups. Results: The mean [standard deviation] accuracy score among all POEMs was 4.2 [0.7], which represents an accuracy of 76% to 99%. Mean comprehensiveness was 47.0% [16.4%]. Mean Flesch-Kincaid Grade Level and Flesch Reading Ease scores were 10.7 [2.1] and 47.9 [10.0], respectively. Mean understandability and actionability were 62.8% [18.8%] and 36.2% [26.5%], respectively. There were no significant differences between accuracy ( P > 0.2), comprehensiveness ( P > 0.5), readability ( P > 0.1), understandability ( P > 0.3), or actionability ( P > 0.2) by authorship. Conclusions: There is wide variability in the quality of cosmetic botulinum toxin POEMs regardless of authorship type. The majority of materials are written above the recommended reading level and fail to include important content points. It is critical that providers take an active role in the evaluation and endorsement of online patient education materials.